HUMAN RIGHTS VIOLATION – IS A NEW BEGINNING POSSIBLE? - Sichel, Ricardo Luiz (Unoesc International Legal Seminar, 2017)
Violation of human rights is unfortunately a common event in human history. The prejudice is based on the false belief of superiority, racism and sexism. There are political movements with the purpose of discriminating an ethical group in order to justify a certain economic or political crisis or even to explain why a certain country is target of terrorism. They become strong based on the fear of the society. People in general become weaker when they are not confident of the future. The purpose of this paper is to analyze if a new beginning is possible. Is a new start with coexistence and a certain level of trust possible? This possibility is discussed in interviews made with survivors of religious or political persecution, published in various newspapers. The important point is the discussion if a new beginning is possible. It is not the question if it is possible to forgive, but how far are future generations morally responsible for these events and don’t allow them to be forgotten in a way to prevent its repetition. Key words: persecution; forgiveness; restart; freedom